Building God's City: The Political Economy of Prayer Camps in Nigeria - Ukah, Asonzeh F. K. (International Journal of Urban and Regional Research, 2016)
The proliferation of religious spaces is a relatively recent development in Nigeria. Nowadays there are more than a hundred religious camps belonging to different religious groups in the country. The most popular of these camps, the Redemption Camp of the Redeemed Christian Church of God, is located 42 kilometres outside of Lagos and measures several thousand acres. Although initially not designed as such, developments in and around Lagos have compelled the managers of the Redemption Camp to present it as an urban alternative to the city of Lagos, which is generally deemed chaotic. The prestige of this camp and its activities have led to expansive urban development that involves the creation of numerous residential estates stretching from Lagos to beyond the Redemption Camp. Based on a recent ethnographic study of the Redemption Camp, this article argues that the process of urban expansion in and around Lagos is propelled by an aggressive form of religious revival that transcends the borders between economics, spirituality and territorial conquest. This article thus illustrates how church-driven, religio-urban developments follow a different logic of city making than often presumed by theorists of African cities, who generally neglect the religious forces that inform urban transformations in Africa. © 2016 Urban Research Publications Limited
Free
Keywords: African city; Lagos; Pentecostalism; housing; neoliberal urbanism; postcolonial city; prayer camps; urban religion; worlding